ANALISIS KONSUMSI PANGAN TINGKAT RUMAH TANGGA DI PROPINSI LAMPUNG - Meliyanah Meliyanah; Suhatmini Hardyastuti; Djuwari Djuwari (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2006)
This research diamed to: 1) knowing the selft-price elasticity, cross-price elasticity and income elasticity of consumption per food item on household level according to location and income level; and 2) knowing the reation between level of income and food consumption on household level according to location and income level.This research used data from SUSENAS of Lmapung Province in 2002 with number of sample of 2091 household, which being differed between rural and urban areas based on low, middle, and high level of income. The data analysis used tobit model and sensored regression.The result showed that: 1) the demand of rice and beeh for household consumption in every level of income in rural and urban areas were inelastic; 2) Coen only been consumed by low income level household in rural areas and the demand was inelastic; 3) the demand of cassava for household consumption on low income level in urban area was elastic, While in middle income level, high income level and every level of income in rural area, cassava demand was inelastic. Cassava was considered as inferior goods; 4) The demand of fish for household consumption an every level of income in rural and urban areas was elastic. Household in rural area on every level of income and in urban areas on middle and high income level consider fish as a main necessity. While on low income level household in urban areas, it was considered as classy/exclusive good; 5) the demand of chicken; for household in rural areas on middle and high income level was inelastic. When in rural low income level and urban middle and high income level, was inelastic chicken meat was considend as classy/exclusive good the rural low income level household; 6) egg demand for household consumption in rural areas on every level of income was inelastic, while in urban area it was elastic for every level income; 7) the rural and urban household on every level of income considered rice as the stpale food; 8) Household in rural and urban areas on middle and high level of income considered beef as main necessity; 9) On household with middle income level in rural areas, egg was considere as inferior good; while an low income level in urban areas, egg was considere as expensive good.